Imidazoquinolines with improved pharmacokinetic properties induce a high IFNα to TNFα ratio in vitro and in vivo - Keppler, Manuel; Straß, Simon; Geiger, Sophia; Fischer, Tina; Späth, Nadja; Weinstein, Thilo; Schwamborn, Anna; Guezguez, Jamil; Guse, Jan-Hinrich; Laufer, Stefan; Burnet, Michael (Frontiers in Immunology, 2023)
TLR Agonists have promising activity in preclinical models of viral infection and cancer. However, clinical use is only in topical application. Systemic uses of TLR-ligands such as Resiquimod, have failed due to adverse effects that limited dose and thus, efficacy. This issue could be related to pharmacokinetic properties that include fast elimination leading to low AUC with simultaneously high cmax at relevant doses. The high cmax is associated with a sharp, poorly tolerated cytokine pulse, suggesting that a compound with a higher AUC/cmax-ratio could provide a more sustained and tolerable immune activation. Our approach was to design TLR7/8-agonist Imidazoquinolines intended to partition to endosomes via acid trapping using a macrolide-carrier. This can potentially extend pharmacokinetics and simultaneously direct the compounds to the target compartment. The compounds have hTLR7/8-agonist activity (EC50 of the most active compound in cellular assays: 75-120 nM hTLR7, 2.8-3.1 µM hTLR8) and maximal hTLR7 activation between 40 and 80% of Resiquimod. The lead candidates induce secretion of IFNα from human Leukocytes in the same range as Resiquimod but induce at least 10-fold less TNFα in this system, consistent with a higher specificity for human TLR7. This pattern was reproduced in vivo in a murine system, where small molecules are thought not to activate TLR8. We found that Imidazoquinolines conjugated to a macrolide or, substances carrying an unlinked terminal secondary amine, had longer exposure compared with Resiquimod. The kinetics of pro-inflammatory cytokine release for these substances in vivo were slower and more extended (for comparable AUCs, approximately half-maximal plasma concentrations). Maximal IFNα plasma levels were reached 4 h post application. Resiquimod-treated groups had by then returned to baseline from a peak at 1 h. We propose that the characteristic cytokine profile is likely a consequence of altered pharmacokinetics and, potentially, enhanced endosomal tropism of the novel substances. In particular, our substances are designed to partition to cellular compartments where the target receptor and a distinct combination of signaling molecules relevant to IFNα-release are located. These properties could address the tolerability issues of TLR7/8 ligands and provide insight into approaches to fine-tune the outcomes of TLR7/8 activation by small molecules.